Insights into How HIAs are Characterized in the Press: Findings from a Media Analysis of Widely Circulated United States Newspapers - Maxim Gakh; Courtney Coughenour; Jennifer Pharr; Aaliyah Goodie; Samantha To (Indiana University-Purdue University Indianapolis, 2017)
Background: Health impact assessments (HIAs) are burgeoning tools in the policy process, where the media plays a critical role by focusing attention on issues, informing consumers, and influencing positions. Examining how media portrays HIAs is critical to understanding HIAs in the policy context. Methods: This study considered how widely circulated, U.S. newspapers represent HIAs. After searching newspaper databases, we used a qualitative document analysis method consisting of open and axial coding to examine specific phrases of HIA depictions.  Results: In coding over 1,000 unique phrases from the 62 documents generated in our search, we found an uptick in HIA-related publications since 2010. Coding these documents identified 46 distinct codes across 10 different themes. The two most prominent HIA-centered themes focused on HIA engagement and the HIA setting. While themes of policy and science, health determinants, and explanations of HIAs were also frequently featured, specific mentions of projected impacts, HIA processes, HIA values, and health outcomes were less prevalent. Conclusions: HIA media portrayals warrant further inquiry from researchers and practitioners. Focusing on how media portrays HIAs is consistent with several HIA steps. It is also important for a broader strategy to educate stakeholders about HIAs and to understand HIAs' utility. HIA practitioners should develop and implement guidelines for media interaction and tracking that encourage practitioners to seek additional media attention and to focus such attention on health impacts and outcomes, HIA recommendations, and HIA values. Building on our work, researchers should examine HIA media portrayals beyond the context of this study.